Role of specific phospholipase D isoenzymes in biological action of jasmonic acid during plant stress responses - Коlesnikov Ya.S.; Кretynin S.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The aim of our investigation was to investigate the role of specific phospholipase D (PLD) isoenzymes in the biological action of jasmonic acid during plant responses to heavy metal stress. Plant growth responses and the PLD activity in vivo are analyzed in Arabidopsis thaliana transgenic plants in order to investigate the role of specific PLD isoenzymes in the biological action of jasmonic acid during the development of plant resistance to heavy metal (copper, cadmium) stress. The results suggest the participation of PLDb in early stages of the biological action of jasmonic acid.